(untitled) (Jurnal Bahasa Lingua Scientia, 2020)
One of the most popular ways of movie translation is subtitling. In order to make a quality subtitle, subtitler should deal with the limited time, limited space, and terminological problems. Special terms, such as automotive term, on subtitling could be found in a family movie. This is a challenge for the subtitler since the terms should be suitable for the audiences in a family movie, i.e. children and teens. This research focuses on: (1) analyzing the translation technique and the translation quality of automotive terms in Cars movie, presented in DVD and in the Internet version, and (2) comparing the quality of the translation of the two versions. This research employs a descriptive qualitative method with the data sources: documents and informants. The research sampling technique is purposive to select the 45 data from the data sources. Data were collected through content analysis, individual interviews, and focus group discussion (FGD). All data are categorized into seven types. They are body part, car brand, car need, car race, engine, process, and miscellany. From the data, this study finds out that there are 12 different techniques applied by the DVD subtitler, compared with 14 different techniques applied by the Internet subtitler. The last finding points out that the quality of DVD translation of automotive terms is more accurate and more acceptable than the quality of the Internet translation. The techniques that produce the high level of accuracy are established equivalent and pure borrowing technique, while the techniques that make acceptable translations of automotive term are established equivalent and generalization technique.